2009
DOI: 10.1016/j.abb.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of mast cell degranulating peptides with model membranes: A comparative biophysical study

Abstract: In the last decade, there has been renewed interest in biologically active peptides in fields like allergy, autoimmune diseases and antibiotic therapy. Mast cell degranulating peptides mimic G-protein receptors, showing different activity levels even among homologous peptides. Another important feature is their ability to interact directly with membrane phospholipids, in a fast and concentration-dependent way. The mechanism of action of peptide HR1 on model membranes was investigated comparatively to other mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Similarly the four peptides in our study presented circular dichroism spectra that are characteristic of helical structures with practically equivalent a-helix content, except for EMP-ER, which showed a higher helical content. The experiments of electrical measurements in planar lipid bilayers of anionic asolectin showed that all the new peptides present a pore-or channel-like activity, in both the positive and negative voltage pulses, as previously demonstrated for eumenitin ), anoplin (dos Santos Cabrera et al, 2008 and other mastoparan peptides (Mellor and Sansom, 1990;dos Santos Cabrera et al, 2009). Channels with lower and higher conductance levels were recorded, but the latter ones were less frequent, and formed only in the presence of the non-amidated Cterminal peptides (eumenitin-R and eumenitin-F).…”
Section: Discussionsupporting
confidence: 74%
“…Similarly the four peptides in our study presented circular dichroism spectra that are characteristic of helical structures with practically equivalent a-helix content, except for EMP-ER, which showed a higher helical content. The experiments of electrical measurements in planar lipid bilayers of anionic asolectin showed that all the new peptides present a pore-or channel-like activity, in both the positive and negative voltage pulses, as previously demonstrated for eumenitin ), anoplin (dos Santos Cabrera et al, 2008 and other mastoparan peptides (Mellor and Sansom, 1990;dos Santos Cabrera et al, 2009). Channels with lower and higher conductance levels were recorded, but the latter ones were less frequent, and formed only in the presence of the non-amidated Cterminal peptides (eumenitin-R and eumenitin-F).…”
Section: Discussionsupporting
confidence: 74%
“…A large number of studies have been devoted, in the last years, to the analysis of the Anoplin secondary structure. Although a quantitative picture is still missing, all the results from these studies support the hypothesis that in water Anoplin is essentially unfolded and that adopts an α‐helical structure in membrane‐mimicking environments . The same studies have also shown a correlation between Anoplin antimicrobial activity and some specific structural–chemical determinants, e.g.…”
Section: Introductionsupporting
confidence: 64%
“…Zeta-potential values reflect the remaining charge density which were neither neutralized nor screened. Changes in zeta potential are used to quantify the extension of the interaction between peptides and phospholipid vesicles and changes in size are related to peptides inducing vesicles aggregation or acting in the detergent mode [39]. In the absence of peptide, AZO vesicles are characterized by an average zeta-potential value of -19.7 ± 0.6 mV (ζ 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…The formation of conductive pores was previously described for other peptides isolated from solitary and social wasp venoms, such as anoplin [61], HR-1 [39], eumenine mastoparan-EF and–ER [34], and eumenitin, eumenitin-F and eumenitin-R [34,62]. Some of these wasp peptides formed rectified pores, whose conductance (or resistance) changes according to the V hold (see [34] Rangel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%